Persepsi Pelanggan terhadap Penerapan Protokol Kesehatan dalam Upaya Meningkatkan Kualitas Pelayanan Selama Era New Normal pada Restoran di Kota Denpasar-Bali - Ni Putu Ariesta Budiani (JURNAL GASTRONOMI INDONESIA, 2021)
In implementing business ethics in the New Normal Era for restaurants, it must follow established health procedures to convince customers that the business sector is in accordance with standards (safety. Therefore, it is necessary to conduct research to determine the extent to which tourism business actors, in this case the food / restaurant service business, have implemented the health protocol. Based on the Guidelines for the Implementation of Cleanliness, Health, Safety and Environmental Sustainability (CHSE) in Restaurants / Restaurants, there are 3 dimensions in implementing health protocols with 33 existing attributes related to service quality to be analyzed. Based on the assessment of 165 respondents spread across 15 restaurants (rated 4-5 star according to TrpAdvisor) in Denpasar, it is concluded that the overall customer perception of the application of health protocols in an effort to improve service quality during the New Normal era, received the average value of 3.34 which in this case is included in the quite good category. This shows that the 15 restaurants representing well-known restaurants in Denpasar have not implemented health protocols optimally. Thus it is suggested that the government immediately hold a consistent and serious socialization and counseling to restaurants.